Nikaia’dan Yeni Yazıtlar IX* - (:unkn) unknown (My University, 2018)
Makalede Nikaia antik kentinin teritoryumunda bulunan 10 yeni yazıt tanıtılmaktadır: 1) Nympheler’e adak; 2) Doktor Agrippa ile eşi Apphe’nin mezarı; 3) Apollonios ve ailesinin mezarı; 4) Apphe’nin mezarı; 5) Aurelius Agathopous’un mezarı; 6) Titus Flavius Helikas ve ailesinin mezarı; 7) II. Hermogenes, III. Hermogenes ile Quintus’un mezarı; 8) Neikandros’un(?) mezarı; 9) Theodoros ve eşi Khrysion’un mezarı; 10) Thallusa’nın mezarı. Roma İmparatorluk Dönemi'ne tarihlenen bu yazıtlar, Bilecik bölgesinden toplanmıştır.

This paper introduces a compilation of 10 unpublished inscriptions found in the territory of the Nicaea: 1) A votive offering of Nymphes; 2) The grave of Doctor Agrippa and his wife Apphe; 3) The grave of Apollonios and his family; 4) The grave of Apphe; 5) The grave of Agathopous; 6) The grave of Titus Flavius Helikas and his family; 7) The grave of II. Hermogenes, III. Hermogenes and Quintus; 8) The grave of Neikandros; 9) The grave of Theodoros and his wife; 10) The grave of Thallusa. The inscriptions dating to Roman Imperial Period were gathered from Bilecik region.
NEW INSCRIPTIONS FROM NIKAIA IX